The effects of adjunctive use of a desiccant agent in the treatment of stage III periodontitis (Randomized controlled clinical trial) - Belal Khalil; Ali Abou Sulaiman; Batoul Al Hajjar (Elsevier, 2023)
Introduction: Several bacterial species inhabiting the dental plaque biofilms are associated with periodontitis. Objective: The main objective of this study was to compare the efficacy of the desiccant agent HYBENX (HBX) as an adjunct to scaling and root planning (SRPX) versus scaling and root planning (SRP) alone in the treatment of periodontitis. Materials and Methods: The study sample comprised 25 patients with periodontitis stage Ш (grades A and B). Each maxillary quadrant was randomly allocated to two groups: SRPX group, including 25 quadrants treated with SRP plus HYBENX, and SRP group, including 25 quadrants treated with SRP alone. The following clinical periodontal parameters were recorded at baseline (immediately after treatment, T0), and 1 month (T1), 3 months (T3), and 6 months (T6) after treatment: probing pocket depth (PPD), relative attachment level (RAL), plaque index (PLI), gingival index (GI), gingival height (GH), and bleeding on probing index (BOP). Results: Comparisons within each study group showed that all clinical parameters significantly improved (P < 0.001) at all follow-up intervals. In contrast, a statistically significant difference (P < 0.001) was observed in RAL, PPD, BOP, and GI indices at all follow-up intervals between the SRPX and SRP groups. In contrast, no significant differences (P > 0.05) were found in GH and PLI between the study groups. Conclusion: Both treatment groups showed improved periodontal parameters. However, applying desiccant gel as an adjunct to SRP was significantly effective in the treatment of stage III periodontitis.